2017
DOI: 10.1128/jvi.01256-17
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Transmissible Gastroenteritis Virus Infection Enhances Enterotoxigenic Escherichia coli K88 Adhesion by Promoting Epithelial-Mesenchymal Transition in Intestinal Epithelial Cells

Abstract: Transmissible gastroenteritis virus (TGEV) is a coronavirus characterized by diarrhea and high morbidity rates, and the mortality rate is 100% in piglets less than 2 weeks old. Pigs infected with TGEV often suffer secondary infection by other pathogens, which aggravates the severity of diarrhea, but the mechanisms remain unknown. Here, we hypothesized that persistent TGEV infection stimulates the epithelial-mesenchymal transition (EMT), and thus enterotoxigenic (ETEC) can more easily adhere to generating cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Considering that the small intestine was the main target organ attacked by TGEV and that IPEC-J2 cells, a spontaneously immortalized cell line from the porcine intestine, are likely much more representative of porcine physiology and the true state of virus infection in animals [25,26], IPEC-J2 cells were used in current study in addition to ST cells. Previous studies showed that IPEC-J2 cells infected with TGEV displayed increased expression levels of proinflammatory cytokines, including IL-1β, IL-6, IL-8, TGF-β, and TNF-α [27,28]. The current study further demonstrated that TGEV could activate NF-κB in IPEC-J2 cells, by using a luciferase reporter gene assay and IFA.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Considering that the small intestine was the main target organ attacked by TGEV and that IPEC-J2 cells, a spontaneously immortalized cell line from the porcine intestine, are likely much more representative of porcine physiology and the true state of virus infection in animals [25,26], IPEC-J2 cells were used in current study in addition to ST cells. Previous studies showed that IPEC-J2 cells infected with TGEV displayed increased expression levels of proinflammatory cytokines, including IL-1β, IL-6, IL-8, TGF-β, and TNF-α [27,28]. The current study further demonstrated that TGEV could activate NF-κB in IPEC-J2 cells, by using a luciferase reporter gene assay and IFA.…”
Section: Discussionsupporting
confidence: 70%
“…Even with the uncertainty regarding the effect of the ZnF, our analyzes, which were performed using truncated mutants allowed us to map the key domain responsible for activating NF-κB to the 120 amino acids of the N-terminal end of the Nsp2 protein. Although the above experiments were conducted in vitro, IPEC-J2 cells are morphologically differentiated cells derived from the small intestine of young piglets, which can be used as a well-defined in vitro model with comparable intestinal physiology [25][26][27][28]. Based on these results, we predicted that Nsp2 could promote intestinal inflammation in TGEV-infected piglets, and the Nsp2-induced inflammation may cause damage of intestine barrier which would benefit the spread of TGEV to deeper intestine tissue.…”
Section: Pk-15 Cells [29] Andmentioning
confidence: 99%
“…Based on our data, IPEC-J2 cells are susceptible to infection with PDCoV, like for the other enteric CoVs, PEDV and TGEV (Guo et al, 2016;Lin et al, 2017;Shi et al, 2017;Xia et al, 2017;Zhao et al, 2014). Compared with LLC-PK or ST cells, our previous study revealed no or less susceptibility of IPEC-J2 cells to PDCoV infection using feces or intestinal contents or tissues of PDCoV-infected pigs (Hu et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…Because of the significant physiologic and morphologic similarities to enterocytes in vivo, this primary cell line has been used increasingly to characterize the interactions of intestinal epithelial cells with enteric bacteria and viruses in vitro. IPEC-J2 cells have been infected with porcine epidemic diarrhea virus (PEDV) and transmissible gastroenteritis virus (TGEV) (Lin et al, 2017;Shi et al, 2017;Xia et al, 2017;Zhao et al, 2014). Compared with PEDV-infected Vero (African green monkey kidney) cells (Guo et al, 2016), the proteomic data from PEDV-infected IPEC-J2 cells appeared to better coincide with the physiologic and pathologic outcomes in PEDV-infected enterocytes in vivo (Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α and IL-1β can activate NF-κB to up-regulate the expression of human FcRn, which enhances FcRn-mediated IgG transport (Liu et al, 2007). TGEV infection was also found to induce EMT via TGFβ in IPEC-J2 cells (Xia et al, 2017). The aim of this study was to identify the TGEV-encoded proteins involved in inducing FcRn production.…”
Section: Introductionmentioning
confidence: 99%